Transmembrane transport and stress response genes play an important role in adaptation of Arabidopsis halleri to metalliferous soils. Issue 1 (December 2018) - Sailer, Christian; Babst-Kostecka, Alicja; Fischer, Martin; Zoller, Stefan; Widmer, Alex; Vollenweider, Pierre; Gugerli, Felix; Rellstab, Christian
Abstract When plants adapt to local environments, strong signatures of selection are expected in the genome, particularly in high-stress environments such as trace metal element enriched (metalliferous) soils. UsingArabidopsis halleri, a model species for metal homeostasis and adaptation to extreme environments, we identifid genes, gene variants, and pathways that are associated with soil properties and may thus contribute to adaptation to high concentrations of trace metal elements. We analysed whole-genome Pool-seq data from two metallicolous (from metalliferous soils) and two non-metallicolous populations (in total 119 individuals) and associated allele frequencies of the identified single-nucleotide polymorphisms (SNPs) with soil variables measured on site. Additionally, we accounted for polygenic adaptation by searching for gene pathways showing enrichment of signatures of selection. Out of >2.5 million SNPs, we identified 57 SNPs in 19 genes that were significantly associated with soil variables and are members of three enriched pathways. At least three of these candidate genes and pathways are involved in transmembrane transport and/or associated with responses to various stresses such as oxidative stress. We conclude that both allocation and detoxification processes play a crucial role inA. halleri for coping with these unfavourable conditions.